Characterization of an accessory plasmid of Sinorhizobium meliloti and its two replication-modules - Luchetti, Abril (2023)
Rhizobia are Gram-negative bacteria known for their ability to fix atmospheric N2 in symbiosis with leguminous plants. Current evidence shows that rhizobia carry in most cases a variable number of plasmids, containing genes necessary for symbiosis or free-living, a common feature being the presence of several plasmid replicons within the same strain. For many years, we have been studying the mobilization properties of pSmeLPU88b from the strain Sinorhizobium meliloti LPU88, an isolate from Argentina. To advance in the characterization of pSmeLPU88b plasmid, the full sequence was obtained. pSmeLPU88b is 35.9 kb in size, had an average GC % of 58.6 and 31 CDS. Two replication modules were identified in silico: one belonging to the repABC type, and the other to the repC. The replication modules presented high DNA identity to the replication modules from plasmid pMBA9a present in an S. meliloti isolate from Canada. In addition, three CDS presenting identity with recombinases and with toxin-antitoxin systems were found downstream of the repABC system. It is noteworthy that these CDS present the same genetic structure in pSmeLPU88b and in other rhizobial plasmids. Moreover, in all cases they are found downstream of the repABC operon. By cloning each replication system in suicide plasmids, we demonstrated that each of them can support plasmid replication in the S. meliloti genetic background, but with different stability behavior. Interestingly, while incompatibility analysis of the cloned rep systems results in the loss of the parental module, both obtained plasmids can coexist together.